APLIKASI PENGELOLAAN ADMINISTRASI KERJA PRAKTIK DAN SKRIPSI BERBASIS WEB DAN MOBILE - Kevin Tjahjadi (Jurnal Ilmu Komputer dan Sistem Informasi, 2018)
Design Application Internship and Undergraduate Thesis of Work Administration Web-Based and Mobile aims to perform internship and undergraduate thesis administration based on procedures applicable in the Faculty of Information Technology Tarumanagara University as well as save the report of internship and undergraduate thesis online. Procedure on the web application is divided into 9 main stages, namely registration, determination of supervisors, internship sessions, trial undergraduate thesis proposal, final hearing of the undergraduate thesis, guidance, assessment, upload and download files. The procedure in mobile application is divided into 3 main stages, namely announcement, schedule of internship session, and schedule of undergraduate thesis trial. Users of the application are divided into 3 categories namely, students, lecturers, and operators (prodi staff, Undergraduate Thesis Coordinator, and Internship Coordinator). The existence of an additional feature is a compression technique that is implemented in the application that is using zip library. The website can be accessed via browser mozilla firefox and google chrome. The mobile app using android based.